Tanggung Jawab Shopee Atas Pelanggaran Hak Cipta Fotografi yang Dilakukan Oleh Kick Avenue dengan Goodshoes - Ayu Fitri Fadilah; Nahrowi; Hendra Pertaminawati (UIN Syarif Hidayatullah Jakarta, 2026)
The main problem in this study is that the element of consumer protection for business actors who do not have a valid license has not been fulfilled by listing photographic works that are not in accordance with the quality of the goods, so that it can be qualified as a violation of photographic copyright and cause losses for consumers in online buying and selling transactions on Shopee. This study aims to find out the protection efforts for aggrieved parties based on the Copyright Law and the Electronic Information and Transaction Law, as well as analyze the legal protection of consumers in online buying and selling transactions on the Shopee platform based on Article 4 paragraph (3) of the Consumer Protection Law. This research employs a normative-empirical legal research method with a qualitative approach, which involves analyzing statutory provisions as the primary basis for the study, combined with an examination of their application in the Kick Avenue and Goodshoes cases through the statute approach and the case approach. The results of the study show that consumers are harmed by merchants on Shopee who use product photos that have the potential to violate photographic copyright and sell goods of different quality from official merchants. Consumers have the right to receive products according to the photo listed, business actors are responsible for losses under the Consumer Protection Law, and Shopee is responsible for supervising and taking action against violations.